A Fault-Tolerant Direct Torque Control for Six-Phase Permanent Magnet Synchronous Motor With Arbitrary Two Opened Phases Based on Modified Variables - Zhou, Yangzhong; Lin, Xiaogang; Cheng, Ming (IEEE transactions on energy conversion, 2016)
A fault-tolerant direct torque control (DTC) strategy for six-phase symmetrical winding shifted-phase 60° permanent magnet synchronous motor with arbitrary two opened phases is proposed in this paper. First, the relationship between flux and electromagnetic torque based on the modified stator flux and modified rotor flux is researched. Second, the optimal control strategy based on the relationship between modified stator voltage vector and modified stator flux on αβ plane, and the relationship between zero-sequence voltage and zero-sequence current is constructed. According to the control strategy, the modified stator flux, electromagnetic torque, and zero-sequence current are controlled by different switching combinations of four-phase inverter bridge. The results of analysis and experiments show that the presented DTC drive system has fast and smooth torque response, and the four-phase stator currents with same peak value are sinusoidal due to the controlled zero sequence current.